Accuracy Verification of Magnetic Resonance Imaging (MRI) Technology for Lower-Limb Prosthetic Research: Utilising Animal Soft Tissue Specimen and Common Socket Casting Materials. (24th April 2012) - Safari, Mohammad Reza; Rowe, Philip; Buis, Arjan
Abstract : Lower limb prosthetic socket shape and volume consistency can be quantified using MRI technology. Additionally, MRI images of the residual limb could be used as an input data for CAD-CAM technology and finite element studies. However, the accuracy of MRI when socket casting materials are used has to be defined. A number of six, 46 mm thick, cross-sections of an animal leg were used. Three specimens were wrapped with Plaster of Paris (POP) and the other three with commercially available silicone interface liner. Data was obtained by utilising MRI technology and then the segmented images compared to corresponding calliper measurement, photographic imaging, and water suspension techniques. The MRI measurement results were strongly correlated with actual diameter, surface area, and volume measurements. The results show that the selected scanning parameters and the semiautomatic segmentation method are adequate enough, considering the limit of clinical meaningful shape and volume fluctuation, for residual limb volume and the cross-sectional surface area measurements.